Pyruvate decarboxylase and its lysine succinylation contribute to the development and metabolite biosynthesis in pathogenic fungus Aspergillus flavus - Guoqi Li; Elisabeth Tumukunde; Yuanyuan Chen; Yao Zhang; Yunlu Kuang; John Adejor; Meifang Wen; Shihua Wang (Mycology)
This study evaluates the effects of pyruvate decarboxylase and its lysine succinylation (Ksucc) on the development of Aspergillus flavus and the production of secondary metabolites. Mutant strains, including the knockout (∆pdc1), pdc1 point mutants (K258R and K258E) and complementary (∆pdc1.com) were constructed. The results showed that both Δpdc1 and K258R strains exhibited decreased conidiophore and conidia production and failed to generate sclerotia. The production of aflatoxin B1 (AFB1) was significantly increased in the Δpdc1 and K258R strains, while it decreased in the K258E strain. The results also indicate that pdc1 and its Ksucc are involved in the stress response and pathogenicity of A. flavus. Through GC-MS analysis, Δpdc1 was found to produce several significantly decreased compounds, including n-hexadecanoic acid, 2-bromotetradecane, and palmitic acid, among others. Additionally, different volatile metabolites, such as 1-iodo-decane, n, n-dimethyloctanamide and n, n-dimethyl-7-octynamide, were not detected in the Δpdc1 strain compared to WT and Δpdc1.com. HPLC results showed that the production of pyruvic acid, malic acid and succinic acid increased in both the Δpdc1 and K258R strains when compared to WT and Δpdc1.com strains. Comparative RNA-seq analysis revealed a total of 3,817 differentially expressed genes (DEGs) including 1,913 up-regulated and 1,904 down-regulated genes in Δpdc1 vs. WT. These results suggest that PDC1 and K258 play a crucial role in the biosynthesis of secondary metabolites, development and stress responses of A. flavus.